Primary open angle Glaucoma - Encinas-Zevallos, Santiago (2023)
Primary open-angle glaucoma is characterized by the progressive and irreversible loss of retinal nerve fibers and retinal ganglion cells, being the leading cause of irreversible blindness in the world. The major risk factor and the only one modifiable is the elevated intraocular pressure, caused by increased resistance to the outflow of aqueous humor through the trabecular meshwork, which causes compression, deformation, and remodeling of the lamina cribosa with the consequent mechanical damage and disruption of axonal transport. Other risk factors are family heredity, age, race, thin central corneal thickness and myopia. Genetic transmission can be of complex inheritance however the genes identified are only present in less than 10% of cases. Diagnosis requires evaluation of the optic nerve head and retinal nerve fiber layer through ophthalmoscopy and by optical coherence tomography, as well as evaluation of perimetry. The only accepted treatment is the reduction of intraocular pressure through medical therapy, laser trabeculoplasty or surgical management.